Personal Data Protection in Digital Business Activities: Corporate Compliance Challenges and Global Consumer Trust Opportunities - Radea Respati Paramudhita (Jurnal Restorasi : Hukum dan Politik, 2026)
The rapid transformation of the digital economy has positioned personal data as both a strategic asset and a significant legal liability. This study aims to analyze the challenges faced by Indonesian corporations in implementing Law Number 27 of 2022 concerning Personal Data Protection (PDP Law) and explore how compliance can be transformed into opportunities to gain global consumer trust. Using normative legal research methods with a statutory and comparative approach, this study identifies key corporate barriers, ranging from the innovation versus security paradox, the burden of administrative sanctions of up to 2% of annual revenue, the need for expert Data Protection Officers (DPOs), to the complexity of cross-border data transfers. The research findings indicate that while compliance requires significant investment, the implementation of Privacy by Design principles and international standards (ISO/IEC 27001) can create strong reputational differentiation. Transparency in data processing has been shown to increase customer loyalty and mitigate long-term legal risks. The study concludes that aligning internal corporate policies with the mandates of the PDP Law is key to mitigating cyber risks while strengthening companies' competitive positions in the global digital supply chain.